2012
DOI: 10.1149/2.022302jss
|View full text |Cite
|
Sign up to set email alerts
|

Eu3+Activated Molybdate and Tungstate Based Red Phosphors with Charge Transfer Band in Blue Region

Abstract: Alkaline earth metal and rare earth tungstate and molybdate compounds are promising candidates as host materials for high efficiency narrow spectral emission red phosphors when activated by trivalent europium (Eu3+). These phosphors emit in the range of 610–620 nm with a full width at half maximum (FWHM) of less than 10 nm, which makes them suitable for use in high color rendering index phosphor-converted white light emitting diodes (pc-WLEDs). However these phosphors suffer from poor excitation using the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(57 citation statements)
references
References 109 publications
1
56
0
Order By: Relevance
“…This can increase the excitation efficiency of the Eu 3? ion, but can be useful only when the electric dipole allowed CT absorption bands are located in spectral ranges where NUV or blue chips emit [152]. As mentioned above, molybdate, tungstate, niobate, and tantalate hosts activated with Eu 3?…”
Section: Red Phosphors-oxide Hosts: Phosphates Silicates Boratesmentioning
confidence: 99%
See 1 more Smart Citation
“…This can increase the excitation efficiency of the Eu 3? ion, but can be useful only when the electric dipole allowed CT absorption bands are located in spectral ranges where NUV or blue chips emit [152]. As mentioned above, molybdate, tungstate, niobate, and tantalate hosts activated with Eu 3?…”
Section: Red Phosphors-oxide Hosts: Phosphates Silicates Boratesmentioning
confidence: 99%
“…As mentioned above, molybdate, tungstate, niobate, and tantalate hosts activated with Eu 3? have been widely investigated [151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166][167], also exploting co-doping with Sm 3? , but only in a limited number of cases the two strategies described above (high Eu 3?…”
Section: Red Phosphors-oxide Hosts: Phosphates Silicates Boratesmentioning
confidence: 99%
“…In this process electron is transfer from the lower energy valence band (formed by 2p orbitals of oxygen atom) to higher energy conduction band (formed by 4d and 5d orbitals of Mo and W respectively). Since Pauling electronegativity of Mo ($2.16) is higher than W ($2.36) [25]; it would be easier for Mo 6+ to get oxidized thereby lowering the Mo 6+ À ÀO 2À bond energy compared to W 6+ À ÀO 2À . Thus an excited state in tungstates is at higher energy position relative to molybdates which can be seen from the excitation spectra 3a and 3b.…”
Section: Excitation and Emission Spectroscopymentioning
confidence: 99%
“…It has been reported that the optical absorption wavelength positions of charge transfers (CT) in MoO x groups depend on coordination number (CN) x [35]. Dutta et al [36] have reported the summary on CT extension methodologies from molybdates with kinds of crystal space group such as tetragonal, hexagonal, monoclinic, orthorhombic, cubic, and triclinic structures. It is important that CNs of Mo in molybdates can shift CT band to longer wavelengths.…”
Section: Uv-vis Optical Absorptionmentioning
confidence: 99%
“…A cubic crystalline phase with MoO 6 groups could provide the longer CT wavelength. So far the longest CT band edge (480 nm) has been reported in cubic molydate host, e.g., (Gd,Y) 6 MoO 6 , which provides CT-absorbing groups of MoO 6 [36]. Molydates with other structure type show shorter CT band edges, for example, 320 nm (from MoO 4 ) in orthorhombic Gd 2 (MoO 4 ) 3 , 330 nm (from MoO 4 ) in tetragonal CaMoO 4 , 400 nm (from MoO 4 ) in monoclinic Gd 2 MoO 6 , 430 nm (from MoO 6 ) in hexagonal Y 6 MoO 6 .…”
Section: Uv-vis Optical Absorptionmentioning
confidence: 99%